2007
DOI: 10.1002/cbdv.200790004
|View full text |Cite
|
Sign up to set email alerts
|

A New Flavone Xyloside and Two New Flavan‐3‐ol Glucosides from Juniperus communis var. depressa

Abstract: A new flavone xyloside, 1, and two new flavan-3-ol glucosides, 3 and 4, were isolated together with three known flavones, 2, 11, and 12, five known flavans, 5-9, and a known dihydrochalcone, 10, from the stems and leaves of Juniperus communis var. depressa (Cupressaceae) collected in Oregon, U.S.A., and their structures were determined on the basis of spectral evidence. A novel flavone nucleus such as that in 1 is seldom found in nature today, and new methylcatechin glucosides 3 and 4 are also rare in nature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Until now the identifications of Juniperus sp. compounds are spread across different reports, in which different species were used and for each only a few number of compounds were identified (Dzharullaeva, 2009;Iida et al, 2007Iida et al, , 2010Lesjak et al, 2011;Lim et al, 2002;Martz et al, 2009;Miceli et al, 2009;Nakanishi et al, 2004;Sakar & Friedrich, 1984;Stassi, Verykokidou, Loukis, & Harvala, 1998).…”
Section: Chemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now the identifications of Juniperus sp. compounds are spread across different reports, in which different species were used and for each only a few number of compounds were identified (Dzharullaeva, 2009;Iida et al, 2007Iida et al, , 2010Lesjak et al, 2011;Lim et al, 2002;Martz et al, 2009;Miceli et al, 2009;Nakanishi et al, 2004;Sakar & Friedrich, 1984;Stassi, Verykokidou, Loukis, & Harvala, 1998).…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…has attracted significant interest (Angioni et al, 2003;Cavaleiro et al, 2001Cavaleiro et al, , 2002Cavaleiro et al, , 2003Rezzi et al, 2001;Salido et al, 2002;Tunalier, Kirimer, & Baser, 2003) much less attention has been paid to other components and there is paucity of detail on the phenolic characterization of Juniperus sp. Previous reports have highlighted the presence of phenolic compounds including flavonoids, neolignans and phenylpropanoids (Iida et al, 2007;Innocenti et al, 2007;Lamerzarawska, 1975;Nakanishi et al, 2004;Sakar & Friedrich, 1984), but also terpenoids (Nunez, Salabarria, Collado, & Hernandez-Galan, 2007;Okasaka et al, 2006;Seca, Silva, Bazzocchi, & Jimenez, 2008). Studies on Juniperus species occurring in Portugal have been even more limited and the focus again was on essential oils (Cavaleiro et al, , 2002(Cavaleiro et al, , 2003.…”
Section: Introductionmentioning
confidence: 96%
“…Although the data about chemical composition of the essential oil from cones and needles of Juniperus plants had already been published (Angioni et al, 2003), only few of the studies investigated chemical constituents other than volatile oils. It was reported that the extracts from Juniperus L. genus contain phenolic compounds, primary flavonoids, neolignans, phenylpropanoids (Abul'saeva and Pashinina, 1981;Iida et al, 2007;Nakanishi et al, 2002), and terpenoids (Topçu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…depressa (Cupressaceae). [2][3][4][5][6] In our continuing study on this plant, two new phenylpropanoid glycosides (1 and 4), were isolated together with six known phenyl propanoides (2, 3, 5-8), two known phenolic compounds (9, 10), and six known lignans (11)(12)(13)(14)(15)(16). This paper describes the structural elucidation of the new compounds as well as the characterization of the absolute structures of three lignans (11,12,14) based on NMR and circular dichroism (CD) spectral evidence.…”
mentioning
confidence: 99%
“…The known compounds were identified as junipediol B 8-O-b-D-glucopyranoside (2), 7) junipediol A 8-O-b-D-glucopyranoside (3), 7) (7S,8S)-guaiacylglycerol (5), 8,9) junipetrioloside A (6), 10) trans-coniferyl aldehyde (7), 11) 2-[4-(3-hydroxypropyl)-2-methoxyphenoxy]-1,3-propanediol (8), 12) vanillin (9), 13) arbutin (10), 13) (2S,3R)-2,3-dihydro-7-hydroxy-3-hydroxymethyl-2-(4Ј-hydroxy-3Ј-methoxyphenyl)-5-benzofuranpropanol 4Ј-O-b-D-glucopyranoside (13), 14) (2R,3S)-2,3-dihydro-3-hydroxymethyl-7-methoxy-2-(4Ј-hydroxy-3Ј-methoxyphenyl)-5-benzofuranpropanol 4Ј-O-b-D-glucopyranoside (15), 15) and cupressoside A (16) 16) by comparison of physical data with literature values and spectroscopic evidence. The structures of the isolates (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) (Table 1). In addition, long-range correlations between H-7/C-1 and H 2 -10/C-3, C-4 were observed in the heteronuclear multiple bond correlation spectroscopy (HMBC) spectrum (Fig.…”
mentioning
confidence: 99%